Islam & Tradisi Budaya di Sulawesi-Selatan - Mardi Adi Armin (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2010)
Islam cannot be separated from the influence of local cultural, either in antithesis or synthesis. There is aculturation process between religion in one hand and culture in other hand. Therefore, the term purification is likely suitable to this case and become interesting discourse along the time. There have been terms Jawa Islam, Iran Islam, Europe Islam, Sunni Islam, etc. In some notes, one of social organization which cannot be tolerant to bid’ah, khurafat, tahayyul practices is Muhammadiyah. By this organization, it is acknowlegded that some element of community began to throw away such this rites. In another perspective, such traditions actually can enrich the local geniun. The national and local culture are parts of Indonesian cultural life.